László Szabó herbologist awarded by „Antal Gulyás medallion for crop protection“ in 2014 (laudation) - Dávid, István; Kiss, László; Kövics, György (Acta Agraria Debreceniensis, 2014)
The Public Utility for Development of Crop Protection Teaching (NOFKA) and The Hajdú-Bihar County Regional Association of Hungarian Chamber of Crop Protection Specialists and Plant Doctors (Chamber) established a joined Award Committee in 2011, which intend to serve as moral appreciation to prominent persons with excellent achievements by awarding the „Antal Gulyás medallion for crop protection” which are available for outstanding teachers, researchers, and practical crop protection specialists. In 2014 László Szabó herbologist has been decorated with the „Antal Gulyás medallion for crop protection” for his “excellence in applied herbology and practical research activity on herbicide applications, moreover for knowledge transfer on weed management”.